The Use of Social Media in Learning English Writing of Indonesian English Department Students - Aprilia Elok Puspita Dewi; Umar Fauzan; Nadia Nadia (Yayasan Visi Intan Permata, 2022)
Social media is a product of information and communication technology that is used by many people around the world, ranging from children to adults. Although not created specifically for educational purposes, social media has drawn the attention of some educators, especially in the field of teaching and learning English. The objectives of this research were to find out the types of social media used by English department students in the fourth semester of UINSI Samarinda and the use of social media in learning English writing. This research was conducted by using a descriptive-qualitative design. The researcher used questionnaires, interviews, and documentation as instruments to collect the data. The primary data in this research was obtained from questionnaires and interviews with the students who were active in using social media in learning English writing. Then, the secondary data contained recordings and documentation obtained from the students as the subjects of this research. The data analysis techniques used were data condensation, data display, conclusion drawing, and verification. To test the validity of the data, the researcher used the credibility technique with the source triangulation method. The result of this research showed that there were seven types of social media used by the students in learning English writing, namely social networking sites (SNS), blogs, micro-blog, wiki, social bookmarking websites, media sharing sites, and RSS (Really Simple Syndication). The students mostly used social media in learning English writing by using some provided features, especially which allow them to interact with their peers, such as personal chat, group chat, comment section, caption, description, story, and bio. Additionally, they also used some of these social media as learning sources to help them in developing their English writing skill.